Selection supplier for Textile and Garment enterprises in Vietnam using association rules - Thi Ha Dinh; Nguyen Thi Thu Thuy; Do Thi Thanh Tam; Nguyen Thi Van Trang; Nguyen Hung Long; Do Van Thanh (Asian Journal of Shipping and Logistics (AJSL), 2024)
The research aims to investigate the support suppliers' decision making for Textile and Garment Vietnamese Enterprises based on using association rules mining. In order to increase the competitive advantage over other enterprises, Vietnamese enterprises are gradually shifting their production methods from CMT (Cut-Make-Trim) to FOB (Free On Board), ODM (Original Design Manufacturing), and OBM (Original Brand Manufacturing). One of the important steps for this transformation is to be self-sufficient in sourcing raw materials from selected suppliers with sufficient capabilities, meeting the requirements of price, and CSR (corporate social responsibility) to enable Vietnamese enterprises to enjoy tax incentives. The Vietnamese Enterprises participate in the textile and garment production process through importing raw materials from other countries such as China, Korea, etc. Therefore, the selection supplier issue is very important to them to enhance their business products. This study researches on finding positive ARs and negative ARs in Textile and Garment data domain via three scenarios to define the relationship of alternative criteria for selection suppliers. By using alternative method of ARM (Association Rule Mining), the experimental results show that Textile and Garment enterprises in Vietnam appreciate the CSR factor highly. This is completely in line with the previous survey research on the new factor in the supplier selection criteria of Textile and Garment enterprises in Vietnam. In another word, in this field, the CSR plays as an important role to reflect company's image and it is the first of decision choice. The other criteria are considered after including Cost, Quality, and Delivery respectively. The remain factors of Service, Capability, Relationship, and Sourcing Country are not highly evaluated via the experiments. With different scenarios along with the association rules mined, they reflect different sets of criteria that textile and garment enterprises use to select their suppliers. Furthermore, the rare rules show situations that are very unlikely but have high reliability in reality. Based on the findings, the factors will show the essentials for suppliers to improve themselves to meet the requirements.
Keywords: 650; Association rules; Selection suppliers; Textile and garment